2017
DOI: 10.1039/c7dt00861a
|View full text |Cite
|
Sign up to set email alerts
|

A Ni2P modified Ti4+ doped Fe2O3 photoanode for efficient solar water oxidation by promoting hole injection

Abstract: Nickel phosphide (NiP) was used as an excellent water oxidation cocatalyst for photoelectrochemical (PEC) water splitting, which could significantly promote the hole injection efficiency and suppress the back reaction of water oxidation over a Ti doped FeO photoanode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Transient photovoltage technique is an effectual method to study the dynamic characteristics of charge transfer behavior, as it could provide the information of carrier generation, separation, and recombination . In detail, under the light irradiation, electrons and holes are excited and gather together at the surface of photocatalyst at the first stage, and therefore the transient photovoltage increases rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Transient photovoltage technique is an effectual method to study the dynamic characteristics of charge transfer behavior, as it could provide the information of carrier generation, separation, and recombination . In detail, under the light irradiation, electrons and holes are excited and gather together at the surface of photocatalyst at the first stage, and therefore the transient photovoltage increases rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Bu et al. introduced Ni 2 P NPs as an outstanding water oxidation co‐catalyst for a Ti 4+ ‐doped Fe 2 O 3 photoanode . The Ni 2 P NPs were deposited on the surface of Ti–Fe 2 O 3 by a simple drop‐casting method and the Ti–Fe 2 O 3 /Ni 2 P photoanode demonstrated a three times enhancement in water oxidation photocurrent density at 1.23 V vs. RHE.…”
Section: Photoelectrocatalysts For H2 Evolutionmentioning
confidence: 99%
“…Reproduced with permission from Refs. and . Copyright 2014 and 2008, respectively, American Chemical Society.…”
Section: Mechanistic Proposalmentioning
confidence: 99%
“…introduced Ni 2 PN Ps as an outstanding water oxidation co-catalyst for aT i 4 + -dopedF e 2 O 3 photoanode. [105] The Ni 2 PN Ps were deposited on the surfaceo fT i-Fe 2 O 3 by as imple drop-casting methoda nd the Ti-Fe 2 O 3 /Ni 2 P photoanode demonstrated at hree times enhancement in water oxidation photocurrent density at 1.23 Vv s. RHE. In light of surface photovoltage (SPV) spectroscopy and open-circuit photovoltage (OPV) results, they concluded that the Ni 2 PN Ps could effectively promote the hole-injection efficiency and suppress the backr eaction of the water oxidation reaction.…”
Section: Photoelectrocatalysts For H 2 Evolutionmentioning
confidence: 99%
“…In conclusion, this Minireview has summarized the application of TMPs as co-catalysts in photocatalytic water splitting reactions. Recently, TMPs have been explored as an excellent catalyst for HERe lectrocatalysis in aw idep Hr ange and have at- [56] and [105].Copyright 2014 and 2008, respectively, American Chemical Society. ChemSusChem 2017, 10,4306 -4323 www.chemsuschem.org tracted much attention.F urthermore, variouss tudies during the past three years have concernedt heir use as co-catalysts for photocatalytic water splitting.…”
Section: Summary and Prospectsmentioning
confidence: 99%